URBANIZATIONS AND SPACES CIRCUMSCRIPTIONS IN SERGIPE (BRAZIL, 1802-1855) (Revista de História Regional, 2022)
This article focuses on the urbanization process of Sergipe, Brazil, in the first half of the 19th century. The objective is to understand the constitution of urban networks and the different meanings linked to urban space, in the legal, administrative and ecclesiastical spheres. The analysis was based on contemporary documentation, such as chroniclers, topographical maps and maps. With these data, it was possible to understand the intra and interprovincial relationships woven up to the mid-nineteenth century.